Ischemia modified albumin levels in patients with insulin resistance (Annals of Medical Research, 2025)
Aim: Insulin resistance (IR) is a crucial characteristic of type 2 diabetes mellitus (T2DM) and can also occur independently or in other conditions such as obesity and metabolic syndrome. Oxidative stress significantly contributes to IR pathology. Ischemia-modified albumin (IMA) is a biomarker of oxidative stress and has been studied for its potential link to IR. This study aimed to identify the relationship between IMA levels and IR.Materials and Methods: We conducted a prospective study involving 101 IR patients without diabetes mellitus and 101 healthy controls. HOMA-IR was used to classify IR and control groups. IMA levels were measured using a colorimetric method. The groups' IMA values were compared, and correlations between IMA and other parameters were determined.Results: There was no statistically remarkable difference in IMA levels between the IR and control groups (p=0.27). In addition, no significant correlation was observed between IMA and HOMA-IR (p=0.60). Significant differences were found in glucose, insulin, and HOMA-IR levels between the IR and control groups (p
Keywords: Insulin resistance; Oxidative stress; Ischemia-modified albumin; HOMA-IR; Type 2 diabetes mellitus